Si-Ni-San Reduces Hepatic Lipid Deposition in Rats with Metabolic Associated Fatty Liver Disease by AMPK/SIRT1 Pathway - Zhang N; Liu T; Wang J; Xiao Y; Zhang Y; Dai J; Ma Z; Ma D (Dove Medical Press, 2023)
Ning Zhang,1,* Tong Liu,1,* Jianan Wang,2,* Yingying Xiao,1 Ying Zhang,1 Jun Dai,1 Zhihong Ma,1,3 Donglai Ma4 1School of Basic Medicine, Hebei University of Chinese Medicine, Shijiazhuang, Hebei, 050200, People's Republic of China; 2Graduate School, Hebei University of Chinese Medicine, Shijiazhuang, Hebei, 050200, People's Republic of China; 3Hebei Key Laboratory of Integrative Medicine on Liver-Kidney Patterns, Shijiazhuang, Hebei, 050200, People's Republic of China; 4School of Pharmacy, Hebei University of Chinese Medicine, Shijiazhuang, Hebei, 050200, People's Republic of China*These authors contributed equally to this workCorrespondence: Zhihong Ma; Donglai Ma, Hebei University of Chinese Medicine, Xingyuan Road 3, Shijiazhuang, Hebei, 050200, People's Republic of China, Tel +86 31189926238, Email mazh1969@163.com; mdl_hebei@aliyun.comBackground: Metabolic associated fatty liver disease (MAFLD) is a chronic disease characterized by excessive lipid deposition in the liver without alcohol or other clear liver-damaging factors. AMP-activated protein kinase (AMPK)/silencing information regulator (SIRT)1 signaling pathway plays an important role in MAFLD development. Si-Ni-San (SNS), a traditional Chinese medicine, has shown reducing hepatic lipid deposition in MAFLD rats, however, the underlying mechanisms of SNS are barely understood.Purpose: The aim of this research was to investigate the mechanisms of SNS in reducing hepatic lipid deposition in MAFLD rats by regulating AMPK/SIRT1 signaling pathways.Methods: The components of SNS were determined by high performance liquid chromatography with mass spectrometry (HPLC-MS) analysis. MAFLD rats were induced by high-fat and high-cholesterol diet (HFHCD), and treated by SNS. SNS-containing serum and Compound C (AMPK inhibitor) were used to treat palmitic acid (PA)-induced HepG2 cells. To elucidate the potential mechanism, lipid synthesis-related proteins (SREBP-1c and FAS), fatty acid oxidation (PPARα and CPT-1), and AMPK/SIRT1 signaling pathway (p-AMPK and SIRT1) were assessed by Western blot.Results: SNS improved serum lipid levels, liver function and reduced hepatic lipid deposition in MAFLD rats. SNS-containing serum reduced lipid deposition in PA-induced HepG2 cells. SNS could up-regulate protein expressions of PPARα, CPT-1, p-AMPK and SIRT1, and down-regulate protein expressions of SREBP-1c and FAS. Similar effects of SNS-containing serum were observed in PA-induced HepG2 cells. Meanwhile, Compound C weakened the therapeutic effects of SNS-containing serum on lipid deposition.Conclusion: SNS could reduce hepatic lipid deposition by inhibiting lipid synthesis and promoting fatty acid oxidation, which might be related with activating the AMPK/SIRT1 signaling pathway. This study could provide a theoretical basis for the clinical use of SNS to treat MAFLD.Graphical Abstract: Keywords: Si-Ni-San, MAFLD, lipid deposition, lipid synthesis, fatty acid oxidation, AMPK